Peran Brand Loyalty, Brand Awareness, dan E-WOM terhadap Purchase Intention pada Klinik Kecantikan - Khoirosita Khoirosita; Dimas Angga Negoro (BADAN PENERBIT STIEPARI PRESS, 2026)
Lifestyle and increasing awareness of the need for facial skin care in Indonesia's tropical climate have encouraged women to seek beauty care solutions, thereby triggering rapid growth in the beauty industry and clinics. This study aims to determine the influence of brand awareness, brand loyalty, and electronic word of mouth (e-WOM) on purchase intention among beauty clinic consumers. The study employs a quantitative approach using a survey method through the distribution of questionnaires, collecting data from 105 respondents selected using purposive sampling. This research model is multiple linear regression, with validity, reliability, classical assumption tests, multiple linear regression equation analysis, partial influence analysis, and determination coefficient analysis conducted. The results of the study indicate that brand awareness and brand loyalty have a positive effect on purchase intention, while e-WOM does not has no effect on purchase intention. These findings suggest that brand loyalty and brand recognition play an important role in driving consumer purchase intention, while information from digital reviews has not yet been able to influence purchasing decisions. This study is expected to contribute to the development of marketing strategies by enhancing brand loyalty and brand awareness and serve as a reference for future research.